Patrimonios espacios y territorios : óptica de la experiencia y prácticas locales en Quibdó 1880-1970 - Rodríguez Echeverry, Natalie, (Colección Encuentros., 2019)
In this work, which is based on heritage architecture and cultural studies, the relationship between communities and habitat is studied to understand their way of conceiving and inhabiting the urban territory. The autor participation in the Plan Especial de Manejo y Protección (PEMP) of the set of architectural assets of Republican architecture of Quibdó led her to question the handling of historical centers containing declared architectural assets in the country. The stories made invisible or denied by hegemonic heritage perspectives were the route charted within the framework of the PhD research project in Social and Human Sciences of the Pontificia Universidad Javeriana. (HKB Translation) --Page 20.